Coastal Hazards Related to Storm Surge - Rick Luettich (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Globally, the risk associated with living in the coastal zone is substantial and rising due to large and growing populations, commerce and infrastructure; relative sea level rise; and the impacts of a warming climate on storm characteristics. The principal coastal hazards in much of the world are storm surge, coastal flooding and surface waves caused by severe tropical or extra-tropical storms. This volume presents state of the art research that extends our understanding of, and our ability to predict coastal hazards that are associated with storm surge. Fourteen papers cover topics ranging from predicting coupled surge and wave dynamics at multiple scales; erosion and scour; statistical considerations for hazard delineation; joint effects of climate change and storm surge; storm surge mitigation strategies and human response to storm surge threats. This work presents important advancements in our ability to predict, mitigate and respond to the principal hazard threatening most of the world's coastal areas. Recognizing these advancements and translating them into policy and practice are essential if we are to effectively manage coastal risk and create more resilient coastal communities in which to live, work and recreate.